Being Human in a Post-Human World: Actor-Network Theory for Anxiety-Induced Meaning-Making in the Existential Shadow of AI - Fry, Alex (Implicit religion, 2023)
As society has become aware of artificial intelligence’s (AI) detrimental social impact, existential anxiety has emerged. Scholarship suggests that such anxiety could facilitate populism, reduced democracy, and social unrest. However, meaning-making reduces existential anxiety, meaning it has potential for addressing this fall out of AI. Public-facing scholarship on AI's detrimental impact is often US- and UK-based. This paper argues that, whilst this literature evinces meaning-making, it fails to offer an explicit framework for doing so. The paper further argues that this occurs alongside the uncritical incorporation of elements from the Judaeo-Christian tradition into meaning-making. These factors potentially limit the efficacy of attempts to assuage AI-induced anxiety in pluralistic Western societies and so this paper considers how the application of insights from Bruno Latour's Actor-Network Theory are well placed to address these shortcomings. Adjacently, the porous boundaries between the so-called religious and non-religious in academic discourse are highlighted via dialogue between meaning-making and a canonical theory in science and technology studies.